Effect of high glucose supplementation on pulmonary fibrosis involving reactive oxygen species and TGF-β - Ning, Wenjuan; Xu, Xiaoxiao; Zhou, Shican; Wu, Xiao; Wu, Hang; Zhang, Yijie; Han, Jichang; Wang, Junpeng (Frontiers in Nutrition, 2022)
This study explored the profibrotic impact of high glucose in the lung and potential mechanisms using latent TGF-β-induced human epithelial cell pulmonary fibrosis and bleomycin (BLM)-induced pulmonary fibrosis models. Results demonstrated that high glucose administration induced epithelial-mesenchymal transition in human epithelial cells in a dose-dependent manner via activating latent TGF-β, followed by increased expression of mesenchymal-related proteins and decreased expression of epithelial marker protein E-cadherin. Further mechanism analysis showed that administration of high glucose dose-dependently promoted total and mitochondrial reactive oxygen species (ROS) accumulation in human epithelial cells, which promoted latent TGF-β activation. However, N-Acetyl-L-cysteine, a ROS eliminator, inhibited such effects. An in vivo feed study found that mice given a high-glucose diet had more seriously pathological characteristics of pulmonary fibrosis in BLM-treated mice, including increasing infiltrated inflammatory cells, collagen I deposition, and the expression of mesenchymal-related proteins while decreasing the expression of the epithelial marker E-cadherin. In addition, high glucose intake further increased TGF-β concentration and upregulated p-Smad2/3 and snail in lung tissues from BLM-treated mice compared to BLM-treated mice. Finally, supplementation with high glucose further increased the production of lipid peroxidation metabolite malondialdehyde and decreased superoxide dismutase activity in BLM-treated mice. Collectively, these findings illustrate that high glucose supplementation activates a form of latent TGF-β by promoting ROS accumulation and ultimately exacerbates the development of pulmonary fibrosis.